2016
DOI: 10.3171/2015.12.peds15448
|View full text |Cite
|
Sign up to set email alerts
|

Using urinary bFGF and TIMP3 levels to predict the presence of juvenile pilocytic astrocytoma and establish a distinct biomarker signature

Abstract: OBJECTIVE The authors report the use of urinary biomarkers as a novel, noninvasive technique to detect juvenile pilocytic astrocytomas (JPAs), capable of distinguishing JPAs from other CNS diseases, including other brain tumors. Preliminary screening of an array of tumors implicated proteases (including matrix metalloproteinases [MMPs]) and their inhibitors (tissue inhibitors of metalloproteinase [TIMPs]) as well as growth factors (including basic fibroblast growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Tissue and urine specimens were collected as previously published 21,23 in accordance with protocols approved by the Boston Children's Hospital IRB (IRB#10-417); informed consent was obtained. Only patients with magnetic resonance imaging (MRI) of the central nervous system were included.…”
Section: Patient Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue and urine specimens were collected as previously published 21,23 in accordance with protocols approved by the Boston Children's Hospital IRB (IRB#10-417); informed consent was obtained. Only patients with magnetic resonance imaging (MRI) of the central nervous system were included.…”
Section: Patient Populationmentioning
confidence: 99%
“…As previously reported by our group and in accordance with an IRB-approved protocol, urine samples were collected preoperatively between 2006 and 2014 21,[23][24][25] . No patient had evidence of other major physiologic stressors, such as stroke, recent surgery, chemotherapy or radiation, at the time of collection.…”
Section: Urine Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with MMPs, urinary TIMPs have also been evaluated as potential biomarkers for juvenile pilocytic astrocytoma (JPA). Multiplexing urinary TIMP‐3 with bFGF could distinguish JPA patients from controls (Pricola Fehnel et al, ). This study found that urinary TIMP‐3 could be a promising biomarker of JPA progression when compared to patients' baseline levels (Pricola Fehnel et al, ).…”
Section: Diagnosis and Prognosis Of Cancers By Mmpsmentioning
confidence: 99%
“…Multiplexing urinary TIMP‐3 with bFGF could distinguish JPA patients from controls (Pricola Fehnel et al, ). This study found that urinary TIMP‐3 could be a promising biomarker of JPA progression when compared to patients' baseline levels (Pricola Fehnel et al, ). In the same study, multiplexing urinary MMP‐13 with bFGF also accurately distinguished JPA from medulloblastoma, a more aggressive tumor compared to JPA (Pricola Fehnel et al, ).…”
Section: Diagnosis and Prognosis Of Cancers By Mmpsmentioning
confidence: 99%